Information System Strategic Plan Design: A Case Study of PT Jasa Marga Tollroad Operator - Henry Aulia Rahman; Muhammad Rifki Shihab; Farisya Setiadi (Green Publisher Indonesia, 2025)
This study aims to design a comprehensive information system strategy for PT Jasamarga Tollroad Operator (JMTO) to enhance operational efficiency, optimize application usage, and support the transition from human-based to technology-based business processes. The research identifies key technology needs within the company through internal and external analyses, including SWOT, Value Chain, and McFarlan’s quadrant. The findings suggest that PT JMTO’s current IT infrastructure and application development processes require improvement to align with long-term business objectives. Using thematic analysis, the study recommends strategies for improving IT governance, data integration, and the development of applications that support operational sustainability. The proposed strategic plan highlights the importance of aligning information system strategies with JMTO’s corporate goals, advocating for better utilization of technology, and providing actionable steps for implementing a more efficient and sustainable IT framework. The implications of this research are significant for PT JMTO as it seeks to modernize its operations, improve service quality, and strengthen its position in the toll road industry. The study also contributes to the field of strategic information systems planning by addressing the challenges of technology adoption in the toll road sector. For future research, examining the effectiveness of these strategies post-implementation and exploring additional external factors impacting digital transformation could provide valuable insights for broader applications in the transportation sector.